1996
DOI: 10.1038/ki.1996.202
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive function in chronic hemodialysis patients

Abstract: We administered a comprehensive neuropsychological test battery, including measures of intelligence, immediate and delayed memory, attention and mental processing speed, language abilities, complex problem solving, motor skills, and depression, to 16 well-dialyzed (Kt/Vurea = 1.46 +/- 0.24) patients with end-stage renal disease (ESRD) and 12 age- and education-matched medical controls. We observed no clear neuropsychological deficits in these ESRD patients who had low average intelligence and limited education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
3
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 33 publications
3
66
3
4
Order By: Relevance
“…In univariate, parsimonious and multivariable models, there were no significant relationships between decreased cognitive function and lower Kt/V. Conclusion: In contrast to several older studies, there is no association between lower other more recent study failed to appreciate a link between dialysis adequacy and cognitive function [16][17][18] . Several of these studies have important limitations: the study of Kutlay et al [16] and colleagues used only the Mini-Mental State Examination (MMSE) for cognitive assessment while Pliskin et al [17] only studied 16 welldialyzed individuals.…”
Section: Introductioncontrasting
confidence: 42%
“…In univariate, parsimonious and multivariable models, there were no significant relationships between decreased cognitive function and lower Kt/V. Conclusion: In contrast to several older studies, there is no association between lower other more recent study failed to appreciate a link between dialysis adequacy and cognitive function [16][17][18] . Several of these studies have important limitations: the study of Kutlay et al [16] and colleagues used only the Mini-Mental State Examination (MMSE) for cognitive assessment while Pliskin et al [17] only studied 16 welldialyzed individuals.…”
Section: Introductioncontrasting
confidence: 42%
“…Some groups of questions can clearly distinct healthy persons from ones with MCI (20). Our findings correlate with other similar studies (21). Level of CRP in our study did not correlate significantly with global cognitive function unlike previous findings (22)(23)(24)(25).…”
Section: Discussioncontrasting
confidence: 54%
“…Early studies among small samples of hemodialysis patients reported moderate rates of cognitive impairment across multiple cognitive domains, but often excluded older patients or those with stroke or severe comorbid conditions (4)(5)(6)(7)(8). One 1997 study using the relatively insensitive Mini Mental State Exam (MMSE) found that 30 percent of 336 hemodialysis patients aged 23 to 93 years had mild to severe cognitive impairment, using very conservative cut-points (9).…”
Section: Prevalence Of Cognitive Impairment In Hemodialysis Patientsmentioning
confidence: 99%